Prioritizing Patani? Indonesian Human Security Diplomacy Towards the Issue of Thailand's Deep South Provinces - Sidik Jatmika; Zain Maulana; Ajeng Puspa Marlinda (Revista UNISCI, 2025)
This study examines the reasons for Indonesian President Jokowi's foreign policy not to prioritise human security diplomacy towards the Patani issue, specifically the acceleration of peace talks between the Thai government and representatives of the combatants from Thailand's Deep South provinces. A qualitative methodology was employed, involving 22 in-depth interviews with elite and grassroots participants from Thailand and Indonesia. These included 7 interviews with State actors and 15 with non-State actors, 4 of whom were combatants. The findings are discussed in relation to the existing literature on the diffusion and implementation of Indonesian human security diplomacy in relation to peace issues in Patani. The article argues for a more proactive and effective diplomacy including the strengthening the role of Islamic non-governmental organisations to help resolve security issues and conflicts there.